Symptom Burden and Quality of Life Among Patients With Heart Failure - Manal Mohammed Al-Sutari PhD, RN; Maysoon S. Abdalrahim PhD, RN (SAGE Publishing, 2024)
Introduction Heart failure is a debilitating condition that is associated with several burdensome symptoms that impede patients' quality of life. However, patients' experience of distressing symptoms and their impacts on their quality of life is not studied in Jordan. Objectives To assess the severity of distressing symptoms and to assess the relationships between these symptoms and the quality of life among patients with heart failure in Jordan. Methods A descriptive cross-sectional design was used. A convenience sampling approach was used to recruit the participants. Heart failure patients (n  =  167) who visited the outpatient clinics in three hospitals in Amman between July and November 2021 were included. The Edmonton Symptom Assessment System and Short-Form 36 tool were used. Results Participants were more likely males with a mean age of 55.2 years (SD  =  13.7). The most distressing symptoms among patients with heart failure were tiredness (M  =  4.56, SD  =  3.24), worse well-being (M  =  4.34, SD  =  2.52), and drowsiness (M  =  3.5, SD  =  3.06), respectively. Symptoms burden were negatively associated with the physical and the mental components summary of the quality of life. Pain, tiredness, nausea, loss of appetite, anxiety, and poor well-being were significant predictors of the physical components. The predictors of the mental components were tiredness, nausea, loss of appetite, and anxiety. Conclusions This study revealed that patients with heart failure facing significant symptom burden. The patients showed inadequate quality of life in both physical and mental components that were inversely associated with symptom burden. Given the debilitating effects of symptom burden on heart failure patients' quality of life, therefore, symptom assessment and management have to be a priority.